EXTERNAL CHARACTERISTICS USEFUL TO DISCRIMINATE THE SEXES OF THE BEETLE COSTALIMAITA LURIDA (LEFÃˆVRE 1891) (COLEOPTERA: CHRYSOMELIDAE, EUMOLPINAE) - Arnhold, Alexandre; DELABIE, Jacques Hubert Charles; GonÃ§alves, Dinarte (REVISTA DE AGRICULTURA, 2019)
The aim of this study was to identify external morphological characteristics allowing sexual differentiation of imagos of the chrysomelid Costalimaita lurida, the most damaging defoliant beetle reported for eucalyptus in Brazil. A study of the external morphological characteristics of this beetle, such as the shape of abdominal urosternites, antennas, presence of tufts and body dimensions, was carried out in 25 adults per sex that were later dissected for gender confirmation. The median length and the pronotum width as well as the sum of the elytra base widths showed significant differences between males and females. Other differences were observed on the abdominal segments of C. lurida, and the dimorphism of the urosternites can be used for the sexing of males and females. Females also present a statistically larger average size than males.